2021
DOI: 10.1002/ccr3.4067
|View full text |Cite
|
Sign up to set email alerts
|

Liver dysfunction associated with hyperthyroidism: Lessons from 2 Case reports

Abstract: Hyperthyroidism may impact liver biochemistry negatively. Clinicians need a high index of suspicion in patients presenting with unexplained deranged liver enzymes or jaundice. Timely initiation of thionamides portends good prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…Moreover, severe LD is a rare but potentially lethal complication of GD, and its treatment is clinically important. Only a few cases of GD with severe LD have been reported to date ( 6 , 7 ), and there is no clear guidance or expert consensus regarding the management of this clinical condition.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, severe LD is a rare but potentially lethal complication of GD, and its treatment is clinically important. Only a few cases of GD with severe LD have been reported to date ( 6 , 7 ), and there is no clear guidance or expert consensus regarding the management of this clinical condition.…”
Section: Introductionmentioning
confidence: 99%
“…(1) direct liver toxicity from exposure of excess thyroid hormones; (2) liver cell degeneration from accelerated decomposition of liver glycogen and protein; (3) congestive hepatopathy from thyrotoxic heart failure; (4) previous underlying liver disease; (5) toxicity and injury by antithyroid medications; (6) autoimmune-related liver injury. 5,6 Retrospective studies also reported that the risk factors of liver dysfunction were age, course of Graves' disesase, heart rate, weight of the thyroid gland, FT4 level, TR-antibodies, and TPO-antibodies. 7 Congestive hepatopathy is described as manifestations of chronic, passive congestion of the liver in the setting of heart failure or other cardiac defects that result in elevation of central venous pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms contribute to liver dysfunction in a state of thyrotoxicosis. These include: 1) direct liver toxicity caused by prolonged exposure to excessive thyroid hormone production, 2) hepatocyte anoxia as a result of the hypermetabolic state, 3) metabolic dysfunction due to liver glycogen and protein decomposition, 4) autoimmune-related liver injury, 5) drugs such as antithyroid medications induced liver injury, and 6) hepatic congestion and hepatic necrosis from thyrotoxic heart failure [16][17][18][19][20][21]. However, because liver dysfunction in Case 2 was too severe to be explained solely by thyrotoxicosis, we speculated that the vaccine might have affected his liver function.…”
Section: Discussionmentioning
confidence: 99%